Ecological drivers of mercury accumulation in oceanic apex predators: A human consumption advisory - de Alencar Goyanna, Felipe A.; Bezerra, Moisés Fernandes; da Silva, Guelson Batista; de Rezende, Carlos Eduardo; Bastos, Wanderley Rodrigues; de Lacerda, Luiz Drude (The Science of the total environment, 2025)
This article provides a detailed assessment of mercury (Hg) concentrations and stable isotopes (δ15N & δ13C) in sharks and pelagic fishes of high trophic level caught in the Western Equatorial Atlantic Ocean and presents advisories for safe consumption by human populations. We found significant differences in Hg concentrations among species, with highest Hg concentrations in Isurus oxyrinchus (2173.6 ± 1521.5 ng g−1) followed by Xiphias gladius (1600.3 ± 671.9 ng g−1) and Prionace glauca (1293.9 ± 830.8 ng g−1), while lowest Hg concentrations were observed in Thunnus albacares (170.0 ± 42.6 ng g−1) and Coryphaena hippurus (190.7 ± 82.8 ng g−1). Intermediate Hg concentrations were observed in T. alalunga (512.9 ± 145.9 ng g−1), Istiophorus albicans (493.1 ± 348.6 ng g−1) and T. obesus (327.7 ± 343.1 ng g−1). The methylmercury proportion relative to total Hg was higher than 80 % for the species C. hippurus, P. glauca, T. alalunga and X. gladius. The δ15N values corroborate with all species occupying upper trophic levels and ranging from 10.2 ± 0.4 ‰ in T. albacares to 12.4 ± 1.1 ‰ in X. gladius. The highest values were observed in I. oxyrinchus, X. gladius and P. glauca, compared to C. hippurus, I. albicans and T. albacares, which showed the lowest δ15N values. The δ13C values ranged from −18.4 ± 2.6 ‰ in X. gladius to −16.6 ± 0.4 ‰ in C. hippurus, with significant differences between the species. We found significant correlations between Hg concentrations and fish weight for all species, except C. hippurus, I. albicans and I. oxyrinchus, indicating the process of bioaccumulation. The significant and positive correlation between log-transformed Hg concentrations and δ15N indicates biomagnification in the upper trophic levels of this oceanic food-web. The estimated species-specific number of meals that are safe for consumption ranged from 0 to 11 meals per month for adults and children. [Display omitted] •Mercury concentrations vary among various oceanic apex predators.•Oceanic apex predators present wide variation of isotopic niche (δ13C and δ15N).•Shark species accumulate the greatest concentrations of mercury.•Exposure estimates and fish consumption advisories are provided for largely commercialized oceanic species.